Study the effect of kidney stones on serum xanthine oxidase, ecto-5’-nucleotidase activity and e3 sumo-protein ligase nse2 (NSMCE2) in Malaysian individuals - Yusof, Faridah; Mehde, Atheer Awad; Mehdi, Wesen Adel; Ghazali, Hamid; Abd Rahman, Azlina (Asian Pacific Journal of Tropical Biomedicine, 2015)
Objective